Social resilience to nuclear winter: lessons from the Late Antique Little Ice Age - Peter Neal Peregrine (Taylor & Francis Group, 2021)
The threat of nuclear winter from a regional nuclear war is an existential hazard that must be actively addressed by policy makers to ensure the shared future of humanity. Here a cross-cultural analysis of 20 societies that experienced the Late Antique Little Ice Age (ca. 536-556CE) is performed in the hope of providing security policy makers with an empirical example of social resilience mechanisms. The climatic conditions of the Late Antique Little Ice Age are strikingly similar to those modelled as resulting from a regional nuclear war employing low-yield nuclear weapons, and thus provides a context in which mechanisms of resilience to nuclear winter might be empirically identified. It is argued that broad political participation fostering bridging ties between communities, agencies, and organisations was a key element of social resilience to the Late Antique Little Ice Age, and may indicate a means to foster resilience to nuclear winter today.